Perspectives of Canadian and American Cat Owners on Provision of Uncontrolled Outdoor Access for Owned Domestic Cats - Tan, Sarah M. L.; Jajou, Sarah; Stellato, Anastasia C.; Niel, Lee (Frontiers in Veterinary Science, 2021)
While uncontrolled outdoor access can increase opportunities for cat physical and mental stimulation, it can also increase risks of injury and illness, and result in predation of wild birds and small animals. In Canada and the United States, it is often recommended to keep cats indoors, but many owners still provide some level of outdoor access. The objectives of this study were to use a cross-sectional survey to explore the attitudes and practices of cat owners in Canada and the United States towards outdoor access and to identify factors that influence the provision of uncontrolled outdoor access. A convenience sample of cat owners (N=7,838) were recruited to complete an online survey, and a mixed logistic regression model was used to examine associations between cat and owner-related factors, and uncontrolled outdoor access for cats, with province/state included as a random effect. In total, 57% of owners kept their cats indoors, and 43% provided some form of outdoor access, with 21% of total owners providing uncontrolled outdoor access. Provision of uncontrolled outdoor access was associated with factors related to cat characteristics (e.g., sex, breed, presence of health and behavioral issues), the home environment (e.g., living with other pets, types of enrichment provided), owner perspectives on outdoor access (e.g., level of agreement with potential benefits and consequence of outdoor access), and owner demographics (e.g., gender, education, area of residence). For cats with uncontrolled outdoor access, few owners reported their cats having a collar or a microchip, suggesting a need to increase education about precautionary measures to protect the welfare of outdoor cats. Results reveal how owners are caring for their cats in terms of providing outdoor access and generate hypotheses for future research to examine the influence of the owner-pet bond and educational programs on owner practices around providing outdoor access.